Consensus Recommendations on the Use of Hyaluronic Acid–Based Fillers for Nonsurgical Nasal Augmentation in Asian Patients. Issue 2 (February 2022) - Trevidic, Patrick; Kim, Hee-Jin; Harb, Ayad; Ho, Wilson W. S.; Liew, Steven
Abstract : Background: Nonsurgical nasal augmentation using dermal fillers such as hyaluronic acid is increasing in popularity because of its less invasive nature and shorter downtime compared with traditional surgery. However, the complexity of the nasal vasculature makes it a high-risk procedure without proper training. Appropriate patient and product selection and safer standardized injection techniques are warranted to minimize complications and to achieve reproducible aesthetic results. In this article, recommendations for nonsurgical nasal augmentation using hyaluronic acid fillers are outlined, with focus on the dorsum, tip, and columella. Methods: A consensus meeting was conducted to develop recommendations on nonsurgical nasal augmentation in Asian patients using hyaluronic acid–based fillers. Literature review was performed using PubMed and Google Scholar. Relevant studies were included to formulate recommendations. Consensus statements were graded using the criteria outlined by the Grading of Recommendations Assessment, Development and Evaluation Working Group. Results: Nonsurgical nasal augmentation is an advanced procedure that warrants in-depth knowledge of the nasal anatomy. The panel recommends thorough preinjection assessment and counseling to fully align the patient's expectations with aesthetic goals. Injections must be deep and at the level of the periosteum or perichondrium to minimize risk of intravascular injection. Aliquots of hyaluronic acid must be introduced using slow, low-pressure, and low-volume injections. Optimal aesthetic effect is achieved with hyaluronic acid dermal fillers that are highly elastic, cohesive, and with good adaptability to their environment. Conclusions: Hyaluronic acid injections are safe and effective in nonsurgical nasal augmentation. In-depth knowledge of vascular anatomy and proper injection techniques using suitable products are necessary to achieve aesthetic goals safely. CLINICAL QUESTION/LEVEL OF EVIDENCE: Therapeutic, V.